The Meaning of Word “al-Nisa” in Toshihiko Izutsu’s Perspective of Semantic - Harahap, Rahma Riani; Pujiati, Pujiati; Zebua, Ali Marzuki (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2020)
The word al-Nisa is often only understood with the meaning of women/female without an understanding that actually the word al-Nisa and its derivation there is a category of meaning that is ignored (distortion). This study aims to discuss the meaning of the word al-Nisa in Al-Quran especially in Surah an-Nisa. The data used are the verses in surah an-Nisa. This research used Izutsu semantic analysis method. The results of this study revealed that the word al-Nisa has two forms in surah an-Nisa, namely Imra'ah or Mar'ah, and Al-untsa. Syntagmatically, the word al-Nisa always encompasses one meaning, namely women, who have female gender. In the term of paradigmatic, the word al-Nisa has the synonymity with the words Imra'ah or Mar'ah, and Al-untsa. Whereas the antonymity of that word is with rijal (male), or ruler. This word was understood as being helpless, weak and oppressed in pre-Qur'anic period. In Al-Qur’anic period, this word was conceived of as a type of gender that is recognized and has an honorable and noble position and has rights as well as men would have. The results of this study are also an effort to find weltanschauung conceptual understanding of the meaning of the word al-Nisa, so the word al-Nisa would not be distorted. It has the evidence that the word al-Nisa does not only distinguish between men and women. Nonetheless, the distinction is only in the terms of function which is conditional.